EVALUASI PENGGUNAAN MEDIA BANTU DALAM PROSES PENYAMPAIAN KIE PENCEGAHAN HIV/AIDS YANG DILAKUKAN ASA PKBI JATENG BAGI SISWA SLTP DAN SMU DI KOTA SEMARANG - Trixie Salawati (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Background: Using media in health education is a way to make people understand more easily about the material given. ASA PKBI JATENG is an NGO specializing in the prevention of HIV ancl AIDS for stuclents of SLTp anct SMU in Semarang. It tries to reach its goal by giving information through communication, information ancl eclucation (KIE) method to students. Since 2003, ASA PKBI never made any evaluation about the effectiveness of supporting media they used for the elucidation. In addition, they never measured the response about the media from their target audience.Parpose: to evaluate the implementation of the media in the presentation conducted by ASA PKBI Central Java ancl to get response from the target audience about the usage of those supporting media. Method: this research is using qualitative method. The data was collected through directed group discussion with interviews to check its validity.Result: the supporting media to deliver in the classroom is by using blackboard. No supporting media is neetlecl when the presentation takes place in the hall. However, there is always a VCD showing at the end of every presentation. Some audience prefer supporting media such as pictures to clarify the KIE presentation. Conclusion: ASA PKBI hasnot optimized the implementation of supporting media such as pictures in presenting their KIE.Keywords: evaluation, supporting media, SLTP and SMU students.